The construction of the idol in the football phenomenon A construção do ídolo no fenômeno futebol - Márcio Pereira Morato; Sérgio Settani Giglio; Mariana Simões Pimentel Gomes (Universidade Estadual Paulista (UNESP), 2011)
This paper objectives to investigate the idol role in the construction of the football phenomenon in Brazil. For that, ex-football players, professional football players and football 5-a-side players were interviewed. The data analysis emphasized four categories: Creation, Diffusion, Idolatry and Roles. To analyze and make inferences from the data, the Enunciation Analysis, one of the Contend Analysis technique was used. The construction of idols was dependent on the appreciation of great achievements and creating bonds. The achievements are dependent on the categories time and space, giving an "expiration date" to idolatry and providing a cyclic renewal of idols. The stronger the relationship of the triad player-club-fan, the deeper the bonds will be. The achievements are "shown" in the media and if the bonds are well established, the image of the idol will be exalted and valued, nurturing and motivating the passion of the fans and cultivating the dream of being a football player in the social imaginary. Este artigo objetivou investigar o papel do ídolo na construção do fenômeno futebol no Brasil. Foram entrevistados ex-jogadores de futebol, jogadores profissionais e jogadores de futebol para cegos. O tratamento dos dados destacou quatro categorias: Criação, Difusão, Idolatria e Papéis. Para tal categorização e inferência foi utilizada a Análise de Enunciação, uma das técnicas da Análise de Conteúdo. A construção de ídolos mostrou-se dependente da valorização de grandes feitos e da criação de vínculos. Os feitos são dependentes das categorias tempo e espaço, dando um "prazo de validade" para a idolatria e propiciando uma cíclica renovação de ídolos. Os vínculos serão maiores quanto maiores forem as relações da tríade jogador-clube-torcedor. Os feitos são "mostrados" na mídia e se os vínculos estiverem bem estabelecidos, a imagem do ídolo será exaltada e valorizada, alimentando e motivando a paixão dos torcedores e cultivando o sonho de ser jogador de futebol no imaginário social.